Strategi pelayanan Account Officer dalam meningkatkan kepuasan calon nasabah : Studi pada El-dinar Finance House - Sarif, Reza (Maliki Interdisciplinary Journal, 2023)
El-dinar Finance House is a community created to accommodate economics faculty students, specifically Sharia banking, in increasing their knowledge of Sharia finance. The activities at El-dinar Finance House are not much different from those in the banking sector. However, according to several economics faculty students, the service provided by El-dinar Account Officer members was less than satisfactory. So this research aims to find out the service strategies implemented by El-dinar Account Officer members to increase prospective customers' satisfaction. The results of this research found that several service strategies implemented by El-dinar Account Officer members to increase prospective customer satisfaction include smiling and greeting (3S), serving on time, speaking clearly, receiving complaints professionally, and being responsible.